The Impact of Entrepreneurship Education on Juvenile Prisoners in 6 Provinces f Indonesia in Covid-19 Era - Hamenda, Bobby; Hamenda, Andress (School of Business, IPB University (SB-IPB), 2024)
Background: During the Covid-19 pandemic, traditional education in Indonesian juvenile prisons faces challenges, hindering inmates' reintegration. Discrimination against ex-convicts seeking employment exacerbates their difficulties post-release. While some organizations offer entrepreneurial training, the lack of standardized programs necessitates further examination of their effectiveness. The pandemic worsens educational deficiencies within prisons, impeding inmates' ability to pursue self-employment upon release. More research is crucial to evaluate the impact of entrepreneurship education, aiding rehabilitation efforts and fostering inmates' business intentions.Purpose: The research presents the impact of entrepreneurship education during Covid-19 era on juvenile prisoners’ entrepreneurial intentions at 6 juvenile prisons located in 6 provinces in Indonesia (Riau, Bangka Belitung, Bengkulu, Lampung, North Sumatera, and Jambi)Design/methodology/approach: Utilising PLS, this quantitative study also analyses prisoners’ entrepreneurial attitude which mediates the impact on prisoners’ intention to be self-employed. The analysis of this study was conducted in January 2023 from 62 questionnaires and found that entrepreneurship education in the 6 juvenile prisons significantly impacts on juvenile prisoners’ entrepreneurial intentions via the essential role of entrepreneurial attitude.Findings/Result: This research discovered that at Indonesian juvenile prisons, prisoners’ entrepreneurial attitude partially mediated the impact of entrepreneurship education on their entrepreneurial intentions. These findings also suggest that Indonesian government should design policy and produce the first national guidelines to set up the standard of entrepreneurship education delivery to the entire juvenile prisons population. The standard education should initially develop the prisoners’ entrepreneurial attitude and other factors which will ultimately improve the entrepreneurial intentions of juvenile prisoners in Indonesia. Conclusion: The research highlights the pivotal role of entrepreneurship education in shaping the entrepreneurial mindset of juvenile prisoners. It stresses the importance of perceiving self-employment as a viable and fulfilling career path, empowering inmates with decision-making capabilities.Originality/value (State of the art): Its novelty resides in its contribution to the scant literature concerning the refinement of entrepreneurial education within Indonesian correctional facilities. It examines the influence of education on the entrepreneurial intentions of juvenile inmates, specifically scrutinizing the mediating role of their entrepreneurial attitudes. Keywords: entrepreneurship education, entrepreneurial attitude, entrepreneurial intentions, indonesian juvenile prisons, covid-19